Investigating face-property specific processing in the right OFA. - Kadosh, K; Walsh, V; Kadosh, R (2011)
Within the neural face-processing network, the right occipital face area (rOFA) plays a prominent role, and it has been suggested that it receives both feed-forward and re-entrant feedback from other face sensitive areas. Its functional role is less well understood and whether the rOFA is involved in the initial analysis of a face stimulus or in the detailed integration of different face properties remains an open question. The present study investigated the functional role of the rOFA with regard to different face properties (identity, expression, and gaze) using transcranial magnetic stimulation (TMS). Experiment 1 showed that the rOFA integrates information across different face properties: performance for the combined processing of identity and expression decreased after TMS to the rOFA, while no impairment was seen in gaze processing. In Experiment 2 we examined the temporal dynamics of this effect. We pinpointed the impaired integrative computation to 170 ms post stimulus presentation. Together the results suggest that TMS to the rOFA affects the integrative processing of facial identity and expression at a mid-latency processing stage.